POTENSI AIR PERMUKAAN DAERAH ALIRAN SUNGAI UNDA UNTUK MEMENUHI KEBUTUHANAIR DOMESTIK DAN NON DOMESTIK DI KABUPATEN KARANGASEM - Gede Agus Bawantu; I Gusti Bagus Sila Dharma; Ni Nyoman Pujianiki (JURNAL SPEKTRAN, 2018)
Karangasem regency, which had a population of 406,600 inhabitants in 2014, still has areas that are prone to water supply to meet the domestic and non-domestic needs. This is proved by the fact that some 16 villages are not served by PDAM network spreading across Selat, Sidemen, Bebandem, Abang and Kubu districts. There is Undawatershed which still has the potential to be developed, in addition to the approximately 90 percent of the watershed area of Unda and springs that provide supply to the area contained in the administrative region of Karangasem regency. The availability of water, was analized using the water balance principle of NRECA and F.J Mock methods as the most appropriate model to the location of study. Synthetic discharge data of the analysis results are used as data in the analysis of mainstay discharge so the potential for surface water that can still be used are known and developed in the Undawatershed. In order to harness the potential of the surface water in the watershed of Unda, the simulation of water allocation of Undawatershed. Based on the results of rainfall data of 2003 to 2014 coupled with the supply of water springs discharge, the average discharge potential of Undawatershed for Q80 is 11.54 m3/sec and for Q90 is 8.97 m3/sec. To plan the utilization and development of surface water potential of Undawatershed, from some of the scenarios that have been made it is known that the potential available in the watershed of Unda can be utilized to meet the domestic and non-domestic water needs of community in five (5) districts suffered from water crisis in Karangasem regency including Selat, Sidemen, Bebandem, Abang and Kubu districts. Keywords: surface water potential, the domestic and non-domestic water needs, utilization and development plan.